Processing of visceral waste proteins of beluga (Huso huso) using Protamex - Esmaeili Molla Abbas (ՀՀ ԳԱԱ հրատ.)
Fish protein hydrolysate (FPH) was produced from the viscera of beluga (Huso huso) by use of bacterial protease Protamex. Hydrolysis conditions (including enzyme activity, temperature, and time) were optimized using response surface methodology (RSM). The optimum conditions to reach the highest degree of hydrolysis were: Բակտերիալ Պրոտամեքս պրոտեազի օգնությամբ թառափի (Huso huso) ներքին օրգաններից ստացվել է ձկան սպիտակուցային հիդրոլիզատ: Հիդրոլիզի պայմաններն օպտիմալացվել են մակերեսային պատասխանի մեթոդոլոգիայով: С помощью бактериальной протеазы Протамекс из внутренностей белуги (Huso huso) получен рыбный белковый гидролизат. Условия гидролиза были оптимизированы с использованием методологии поверхностного ответа (МПО).
Keywords: Biology; Biochemistry; Biotechnology